Kinetic resolution of alpha-acetoxy carboxylic acids with homochiral SuperQuats. - Bew, S; Davies, S; Fukuzawa, S (2000)
Preliminary investigations focused on the kinetic resolution of (+/-)-alpha-acetoxy mandelic carboxylic acid chloride with isopropyl SuperQuat and isopropyl Evans' homochiral auxiliaries. The addition of 2 equiv. of the acid chloride to the lithium salts of the auxiliaries (SuperQuat and Evans') at -100 degrees C in the THF afforded the corresponding N-acyl auxiliaries in high chemical yields (95% and 89%) and d.e.'s of 66% and 40%, respectively. Using the same mandelic acid chloride but incorporating SuperQuat auxiliaries derived from (S)-phenylglycine and (S)-phenylalanine yielded the corresponding N-acyl SuperQuats in 86% and 90% and d.e. 's of 66% and 30%, respectively. Substituting the phenyl group within the alpha-acetoxy mandelic acid chloride for a n-butyl, tert-butyl and cyclohexyl group changed the d.e. significantly when kinetically resolved with isopropyl SuperQuat. The yields were all similar, i.e., approximately 90% but the d.e.'s varied considerably, with values of 20%, 50%, and 82%, respectively. Attempted kinetic resolution of alpha-methoxyphenylacetyl chloride using the lithium salt of isopropyl SuperQuat revealed a diasteroselectivity of 45%, significantly lower than that obtained with the corresponding alpha-acetoxy carboxylic acid chlorides.